Trends in franciscana (Pontoporia blainvillei) stranding rates in Rio Grande do Sul, Southern Brazil (1979-1998) - Pinedo, M.C.; Polacheck, T. (J. Cetacean Res. Manage., 1999)
For over twenty years incidental takes of the franciscana, Pontoporia blainvillei, in coastal artisanal gillnet fisheries have been documented from strandings in Rio Grande do Sul, Southern Brazil (29°20’S to 33°45’S). No direct measures of fishing effort exist for these artisanal gillnet fisheries. However, the fisheries are known to have increased substantially since the early 1980s. Indicative fishing effort in the artisanal bottom gillnet fishery was calculated from the available time series of CPUE from industrial trawl fisheries combined with estimates of the annual catch from the artisanal fisheries. The resulting time series indicates that effort was generally increasing throughout the period. Trends in stranding rates of franciscana were analysed for the 1979-1998 period from systematically collected data as part of a long-term beach monitoring programme for marine mammals. Strandings of franciscana generally occur during spring, from September to December. This is the main period when the artisanal bottom-tending gillnet fisheries are active. However, strandings have occurred in all months, indicating that at least some franciscanas remain in the area year-round. Strandings rates for the spring months were generally high during 1979-81, declined to relatively low levels during 1982-85, increased again until 1987 and subsequently declined, with perhaps some increase again in the most recent years. While clearly recognising the limitations of attempting to infer changes in abundance from strandings data, one of the most likely explanations for declining stranding rates in the face of substantially increasing fishing effort would be a decline in franciscana abundance. As such, the strandings rate trends in conjunction with the effort trends, are a matter of concern and the available information, while limited, suggests that an impact on the southern Brazil population may have occurred.